The Transition from Crawling to Walking: Can Infants Elicit an Alteration of Their Parents’ Perception? - Longobardi, Claudio; Quaglia, Rocco; Settanni, Michele (Frontiers in Psychology, 2016)
Our study was designed to address a gap in the literature on parents’ perception and motivation to protect their infants from potential risk of injury in the transition from crawling to walking. The participants were 260 Italian subjects, of whom 158 were women and 102 men, aged between 20 and 45 years. They were asked to draw two domestic objects to assess the possible alterations in the perception of environmental elements seen by the parents as a potentially dangerous cause of unintentional injury for their child. Analysis showed that the group of mothers with children aged 9 to 18 months had drawn the largest tables, while the table areas of the other two categories of women were much smaller. Concerning males, the group that drew the largest tables was the one with children, but not in the age range of 9-18 months, while there was no great difference between the other two groups. The final descriptive analysis concerned the average scores on the STAI-Y tests both for state and trait anxiety. In all groups a substantial parity was observed, except for the non-parent men, who had a lower a lower level of state anxiety. Both the fathers and the mothers of children of 9-18 months obtained lower scores, both for state and trait anxiety. Based on the findings, we demonstrate that children transitioning from crawling to walking can elicit a perceptive reactivity their mothers, which satisfies their natural need to protect their offspring.